2002
DOI: 10.1007/bf03326409
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of neutrophil elastase in impaired mucosal repair in patients with ulcerative colitis

Abstract: HGF produced in the intestinal mucosa may be an important stimulator acting on epithelial cell restitution in patients with IBD. However, NE released in situ may impair mucosal repair through inhibiting epithelial cell proliferation in patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…On the contrary, HNE has been proposed as a marker 12 and a therapeutic target for UC. 13,14 Moreover, HNE by cleaving key receptors such as CD14 may be responsible for the impaired apoptotic cell recognition by macrophages, thereby prolonging inflammation. 15 Taken together, augmentation of these inhibitor activities seems intuitively promising as a novel targeting therapy against active UC.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, HNE has been proposed as a marker 12 and a therapeutic target for UC. 13,14 Moreover, HNE by cleaving key receptors such as CD14 may be responsible for the impaired apoptotic cell recognition by macrophages, thereby prolonging inflammation. 15 Taken together, augmentation of these inhibitor activities seems intuitively promising as a novel targeting therapy against active UC.…”
Section: Discussionmentioning
confidence: 99%
“…35,41 Briefly, 4-µm-thick cryostat sections were fixed in acetone at room temperature for 15 min and incubated with normal goat serum diluted 1 : 40. The sections were incubated with a combination of the anti-human IL-15Rα polyclonal antibody, H-107 (1 : 40 dilution) and the monoclonal antibody (1 : 50 dilution), L-26 (anti-CD20; Dakopatts) or UCHT-1 (anti-CD3; Dakopatts), followed by incubation with the fluorescein isothiocyanate (FITC)-conjugated Fab fraction of goat anti-mouse IgG (Jackson ImmunoResearch Laboratories, West Grove, PA, USA) and lissamine rhodamine-conjugated Fab fraction of goat anti-rabbit IgG (Jackson ImmunoResearch Laboratories).…”
Section: Histologymentioning
confidence: 99%
“…[9][10][11] It has also been demonstrated that the plasma NE level is correlated with the clinical activity of UC. 9,12 However, a definitive conclusion cannot be Background.…”
Section: Introductionmentioning
confidence: 99%